The Role of Non-Governmental Organizations (NGOs) in Regional Development: Contributions, Collaborations, and Challenges - Dilnawaz, Abid Ahmad; Pasaribu, Dzulqarnain Hapotan (Kampret Journal, 2025)
Non-Governmental Organizations (NGOs) play a crucial role in regional development by addressing social, economic, and environmental challenges that governments and the private sector may not fully address. This study examines the contributions of NGOs to regional development, their collaboration with governments and private entities, and the challenges they face. Using a qualitative research approach, data was collected through case studies, interviews, and literature analysis to assess the effectiveness of NGO interventions. The findings indicate that NGOs significantly contribute to poverty alleviation, education, healthcare, and environmental sustainability. Their collaborations with governments enhance policy implementation, while partnerships with private entities provide funding and technical support. However, NGOs also face challenges such as political interference, regulatory restrictions, and financial sustainability issues. The study highlights the increasing use of digital technologies, social enterprises, and innovative funding models to improve NGO operations and ensure long-term impact. Comparing this study with previous research, it is evident that while traditional NGO roles remain relevant, the strategies and operational models have evolved. Community-driven development remains effective in rural areas, whereas hybrid models involving government and private sector partnerships work better in urban contexts. The study concludes that strengthening multi-stakeholder partnerships, improving financial sustainability, and maintaining NGO independence are essential for maximizing their impact on regional development. Future research should explore long-term sustainability strategies and assess the role of technology in enhancing NGO effectiveness.